New plant fossil records and palaeoecology of the Uspallata Group (Late Triassic) at Cacheuta Hill, Cuyo Basin, west-central Argentina - Bodnar, Josefina (2020)
The Triassic sedimentary rocks outcropping in the Cacheuta Hill (Precordillera, Mendoza province, Argentina) correspond to the upper part of the Uspallata Group (Late Triassic) comprising the younger levels of Potrerillos Formation, and the Cacheuta and Río Blanco formations. In this contribution, new fossil plant records in the Uspallata Group are described, the systematic palaeontology of previously described taxa is revised, and the plant-palaeocomunities are reconstructed. In addition, the studied unit is correlated with other Triassic formations of Gondwana. Our revision of the plant-fossil record from the Uspallata Group provides: the first record of the genus Androstrobus (Cycadales) and the genus Odyssianthus (Voltziales) in the Argentinean Triassic, the description of Rissikianthus as a new element of the Cacheuta palaeoflora, the transfer of Baiera rollerii to Rochipteris rollerii, and the presence of Hamshawvia and Stachyopitys in the Argentinean Triassic, which confirm the record of these reproductive structures as related to the ginkgoalean lineage. The most diverse plant fossil group in the Triassic of Cacheuta Hill is the seed fern order Umkomasiales (= Corystospermales). Four types of plant palaeocommunities were inferred for Uspallata Group: conifer-dominated deciduous forests, corystosperm-dominated deciduous forests, corystosperm-dominated evergreen forests, and corystosperm-dominated shrubby-arboreal. These palaecommunities were developed in mixed load meandering fluvial, palustrine and meromictic lacustrine systems under seasonal or oceanic subtropical climates, varying from semiarid to humid environments. The plant fossil assemblages present in the Uspallata Group at Cacheuta Hill shows similarities with the Molteno Formation from South Africa, indicating a Late Triassic (Carnian–Norian) age for the unit.